Lei de acesso à informação: análise da transparência ativa em instituições federais de ensino superior do Estado da Paraíba - Santiago, Lucas Carneiro Guedes (2020)
With the promulgation of the Federal Constitution of 1988 and, later, of the Law on Access to Information (LAI), in 2011, the public information produced and maintained by the State is now recognized as of collective interest. In this sense, the right of access to public information is understood as a democratic device, which allows the citizen to participate in activities arising from the public administration, even controlling them. Lai deals with numerous norms, however, in this research, the requirement of the use of active transparency by public entities was emphasized. Active transparency occurs when the State proactively discloses information of collective interest on official websites, without any kind of questioning on the part of citizens. In this context, this research addressed the active transparency of information in the Federal Universities of the State of Paraíba, with the general objective of analyzing active transparency, at UFPB and UFCG, based on what the Active Transparency Guide prescribes. This study, with a qualitative and descriptive approach, was developed from documentary and field research (using the techniques of systematic observation) and interview. Finally, content analysis by categorization was applied to treat and analyze the collected data. The results of the research showed that the Federal Universities of Paraíba behave as social institutions that produce, mediate and disseminate their information. The public entities presented two different scenarios, in which the UFCG exhibits low rates of attendance to the GTA, and the UFPB demonstrates excellent positive indicators. It was perceived the commitment of the institutions to apply, in the best possible way, the policies related to access to information, in order to meet the current legal norms. It was identified that the challenges faced daily in universities are similar, highlighting as barriers to achieving the guidelines proposed in the legislation the following contexts: the lack of sensitivity of managers, organizational culture of secrecy, lack of knowledge of public agents about LAI and internal communication of the institution. All these points were recognized from the discourses of the research subjects. In this sense, we highlight the effort of the servers directly responsible for LAI in seeking to meet the regulations as much as possible. It was noted that the actions and services provided by universities become capable of influencing the social context of the citizen, and the teaching, research and extension activities carried out by educational institutions strengthen the exercise of citizenship. Thus, we began to see access to public information as a social good and a collective right. Finally, we emphasize the importance of effective policies related to informational transparency, with the objective of fostering citizenship and encouraging citizens to participate effectively in the actions practiced by the State.